A PBL-Based Circulatory System E-Module Based on Research Results to Improve Students’ Critical Thinking Skills and Cognitive Learning Outcome - Rahmatika, Helsa; Lestari, Sri Rahayu; Sari, Murni Sapta (JPI (Jurnal Pendidikan Indonesia), 2020)
The low of students’ critical thinking skills and cognitive learning outcomes can be caused by learning difficulties. One of the causes is the lack of availability of learning resources that are relevant and easily applied. The aim of this research is to produce a Problem Based Learning-based e-module based on the results of research that is valid, practical, and effective. The development model used is ADDIE with stages are analyze, design, develop, implement, and evaluate. The resulting e-module is very valid and very practical with the validation value by content expert=100%, learning expert=98,65%, field practitioners=92,85%, and then the value of practicality=86,99%. The result of quade’s rank analysis of covariance test with p-value is 0,000<α (α=0.05) and the result of ANCOVA test with p-value is 0,000<α. The conclusion is Problem Based Learning-based e-module based on the results of research can improve critical thinking skills and cognitive learning outcomes of students.